Spatial-temporal dynamics of qualitative changes in efficiency of agricultural production in agricultural holdings of Ukraine in 2015 and 2019 - Melnychenko, S.; Morozova, O.; Bohadorova, L. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2021)
The agricultural holdings are one of the most common types of agricultural enterprises in Ukraine. The experience of foreign countries shows that the agricultural holdings should be the basis for the formation and effective development of agricultural industries in the country. They are one of the effective forms of management with the appropriate level of organization of the production technological processes and optimal territory order. However, rapid market transformations and the economic crisis in recent years have had a negative impact on the activities of the agricultural holdings. Theoretical aspects of the agro-industrial complex study, in particular the crop industry of Ukraine are covered in the works of the following homeland scientists: Malik M.Yo., Shpykuliak O.H., Tabinskyi V.A., Koliesnik Ye.O., Silina I.S., Urkevych V.Yu., Mokhnenko A.S. and others. Significant number of problems, such as low level of specialization; insufficient level of development of production, processing and marketing infrastructure; imperfect structure of production and its material and technical support affects the formation of the competitiveness of the agricultural holdings in the homeland market. To solve these problems requires scientific development and practical implementation of a set of measures that will improve the efficiency of the agricultural holdings. The purpose of the article is to study the spatial-temporal trends in the efficiency of the crop branch development in the agricultural holdings of the regions of Ukraine. The object of the research is the plant branch of Ukraine. The subject of the study is the spatial-temporal trends in the efficiency of the crop branch development of the regions of Ukraine. During the research, the statistical data of spatial-temporal activity of the agricultural holdings in the context of regions for 2015 - 2019 were used. Previous scientific works of homeland scientists were also used. During the study, we used the following methods: statistical, cartographic and comparative-geographical. Agricultural production is influenced by many different factors that determine the peculiarities of its functioning (natural-geographical and socio-geographical). The territory of Ukraine has a favorable geographical, transport and geopolitical position. Demographic features of rural areas have negative trends, which in turn is a factor that determines the agricultural production of the territory. Therefore, all measures must be taken to stabilize the demographic situation in rural areas. Natural-geographical factors include climate and agro-climatic resources, which throughout Ukraine are very favorable for the crop branch development. Despite the favorable conditions for the development of the agricultural complex, in recent years throughout Ukraine there has been a negative trend of reducing the efficiency of crop production. Therefore, the study of spatial-temporal dynamics of sectoral and intra-sectoral specializations and the identification of territorial imbalances in agricultural land use of Ukraine, their causes and solutions is a very important scientific problem today. To increase economic efficiency and smooth operation of the agricultural holdings, our country must take the following measures: improving the legal framework; quality training of qualified personnel; updating the material and technical base; providing long-term and low-interest loans; irrigation system upgrades, etc.